2002
DOI: 10.1046/j.1468-3083.2002.00546.x
|View full text |Cite
|
Sign up to set email alerts
|

Erythema annulare centrifugum: report of a case with neonatal onset

Abstract: Darier's erythema annulare centrifugum (EAC) is often associated with infectious, autoimmune or neoplastic disease, nevertheless, most cases of EAC remain unexplained. We report a case of EAC with neonatal onset and a clinical course of over 20 years. The patient presented from the 6th day of life with erythematous papules that enlarged centrifugally to form figurate, annular or policyclic plaques involving the entire cutaneous surface. The clinical picture had a chronic course, disappearing only during unrela… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
7
0
2

Year Published

2008
2008
2019
2019

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 28 publications
1
7
0
2
Order By: Relevance
“…Interestingly, our patient presented a complete resolution of the lesions only during febrile episodes. Such a phenomenon has been previously described by Wong et al in a patient suffering from AEI and by Guillet et al and Bottoni et al in patients suffering from EAC (20,22,23). It is possible that the patients suffering from annular erythemas, which are inflammatory dermatoses, have a dysregulation of cytokine production in the skin and so the natural increase of interferon (IFN) which usually occurs when body temperature is higher than normal may cause a normalization of such alteration, with resolution of the skin lesions.…”
Section: Discussionsupporting
confidence: 56%
“…Interestingly, our patient presented a complete resolution of the lesions only during febrile episodes. Such a phenomenon has been previously described by Wong et al in a patient suffering from AEI and by Guillet et al and Bottoni et al in patients suffering from EAC (20,22,23). It is possible that the patients suffering from annular erythemas, which are inflammatory dermatoses, have a dysregulation of cytokine production in the skin and so the natural increase of interferon (IFN) which usually occurs when body temperature is higher than normal may cause a normalization of such alteration, with resolution of the skin lesions.…”
Section: Discussionsupporting
confidence: 56%
“…The prevalence and incidence of EAC are unknown. Adults are the most commonly affected population, but it may also occur in children, and a case of neonatal EAC was reported . Retrospective studies have shown that EAC ages of onset usually range from 5 to 90 years, with a mean age of onset of 40–50 years …”
Section: Discussionmentioning
confidence: 99%
“…In the literature is reported the possible association between this disease and estrogens; 9 we also described a case of EAC with neonatal onset in a boy with testosterone low serum values, who developed primary genital infantilism with hypogonadism 10 …”
mentioning
confidence: 83%